2021
DOI: 10.4209/aaqr.210206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PM2.5 Chemical Composition and Air Quality Monitoring: Implications of Air Pollutants Emissions from a Night Market in Kaohsiung City, Taiwan

Abstract: There are around 300 night markets in Taiwan, and they have been drawing an increasing number of tourists in recent years. As a result, public awareness over air quality in the night markets has grown tremendously. In response to this, a specific night market in Kaohsiung City was chosen for this study in order to characterize the existing air quality in and around the night markets. In this present study, we employed an Industrial Source Complex Short-Term (ISCST3) air quality model for the simulation of PM2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Zhao & Lin (2010) characterized the air quality in night markets and demonstrated that the levels of CO, CO 2 , particulate matter with an aerodynamic diameter smaller or equal to 10 μm (PM 10 ), particulate matter with an aerodynamic diameter smaller or equal to 2.5 μm (PM 2.5 ), formaldehyde (HCHO), and polycyclic aromatic hydrocarbons (PAHs) at night markets were all higher during open hours than those during nonoperation hours. Amesho et al (2021) assessed PM 2.5 in a night market and obtained similar results. Que et al (2019) studied carbonyl compounds in cooking oil fumes in night markets and found that high emissions of carbonyl compounds could increase the cancer risk due to workplace exposure.…”
Section: Introductionmentioning
confidence: 62%
“…Zhao & Lin (2010) characterized the air quality in night markets and demonstrated that the levels of CO, CO 2 , particulate matter with an aerodynamic diameter smaller or equal to 10 μm (PM 10 ), particulate matter with an aerodynamic diameter smaller or equal to 2.5 μm (PM 2.5 ), formaldehyde (HCHO), and polycyclic aromatic hydrocarbons (PAHs) at night markets were all higher during open hours than those during nonoperation hours. Amesho et al (2021) assessed PM 2.5 in a night market and obtained similar results. Que et al (2019) studied carbonyl compounds in cooking oil fumes in night markets and found that high emissions of carbonyl compounds could increase the cancer risk due to workplace exposure.…”
Section: Introductionmentioning
confidence: 62%
“…The formation of toxic PAHs is closely related to vehicular exhaust from incomplete combustion. Substantial contributions from traffic emissions lead to an increased probability of developing respiratory allergy and lung cancer (Amesho et al, 2021;Xu et al, 2021;Wang et al, 2021b). The index for health risk assessments such as ILCRs and BaPeq are used to evaluate the cancer risk of PAHs.…”
Section: Pm25 and G-pahs Health Risk Assessmentsmentioning
confidence: 99%
“…Studies have found that concentrations of air pollutants such as carbon monoxide (CO), carbon dioxide (CO₂), particulate matter 10 (PM10), particulate matter 2.5 (PM2.5), formaldehyde (HCHO), and polycyclic aromatic hydrocarbons (PAHs) during the operating period of the night market were higher than during the non-operating period due to cooking activities, with barbecue activities cause the most severe air pollution [18]. In addition, the dumping of organic wastes into the environment might contribute to global warming, and policy actions were needed to target air pollution problems at different levels of management to create synergistic effects and reduce the impact of climate change [19,20]. Existing studies involving the night market area included solid waste recycling from garbage bins [21], wastewater pollution generated [5], hazards of exhaust gases generated [18,22,23], sources of electricity for operations [6], tableware materials [24], dangers of plastic packaging for hot food [25], perceptions of using plastic packaging [26], willingness of merchants to have environmentally friendly packaging [10], and biodegradation potential of recycled wastes [27].…”
Section: Introductionmentioning
confidence: 99%